2019
DOI: 10.1021/acs.langmuir.9b02927
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the Molecular Characteristics of Molecularly Imprinted Polymers as Monitored by Sum Frequency Generation Spectroscopy

Abstract: Sensing in molecularly imprinted polymers (MIPs) requires specific interactions of the imprinted polymer and the approaching template molecule. These interactions are affected by the morphology of the polymer surface, the affinity of the template molecule to the polymer network, and the steric approach. In this particular study, a template molecule, metronidazole, is studied with respect to the typically used methacrylic acid-based imprinted polymer using a combination of bulk and surface techniques. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
(85 reference statements)
0
13
0
Order By: Relevance
“…Sum frequency generation (SFG) vibrational spectroscopy is a second-order nonlinear optical spectroscopic technique, which is capable of detecting the presence, coverage, and orientation of functional groups at surfaces and interfaces including buried solid/solid interfaces in situ . Because of the selection rules of a second-order nonlinear optical process, only surfaces and interfaces without inversion symmetry can generate SFG signals, avoiding the interference of signals generated from the bulk material. SFG has excellent sub-monolayer surface/interface specificity and has been developed into a powerful technique to investigate molecular structures at the buried polymer interfaces. ,, Many traditional surface-sensitive analytical techniques (e.g., XPS) require debonding of composite parts to obtain structural information of the original buried interface, which may destroy information about the original interface . Practically, good adhesion is often defined by the observation of cohesive failure of the adhesive or substrate, which occurs because the interface is sufficiently strong so that it cannot be separated cleanly.…”
Section: Introductionmentioning
confidence: 99%
“…Sum frequency generation (SFG) vibrational spectroscopy is a second-order nonlinear optical spectroscopic technique, which is capable of detecting the presence, coverage, and orientation of functional groups at surfaces and interfaces including buried solid/solid interfaces in situ . Because of the selection rules of a second-order nonlinear optical process, only surfaces and interfaces without inversion symmetry can generate SFG signals, avoiding the interference of signals generated from the bulk material. SFG has excellent sub-monolayer surface/interface specificity and has been developed into a powerful technique to investigate molecular structures at the buried polymer interfaces. ,, Many traditional surface-sensitive analytical techniques (e.g., XPS) require debonding of composite parts to obtain structural information of the original buried interface, which may destroy information about the original interface . Practically, good adhesion is often defined by the observation of cohesive failure of the adhesive or substrate, which occurs because the interface is sufficiently strong so that it cannot be separated cleanly.…”
Section: Introductionmentioning
confidence: 99%
“…SFG vibrational spectroscopy (or SFG in short) is a second-order nonlinear optical technique which is submonolayer surface sensitive because of its special selection rule: under the electric dipole approximation, SFG signal can only be generated from a medium with no inversion symmetry. SFG probes the macroscopic second-order nonlinear susceptibility χ (2) of a material, while χ (2) is nonzero only for a sample with no inversion symmetry. , Most bulk media are centrosymmetric, thus do not have SFG signal, while surfaces and interfaces lack inversion symmetry and can generate SFG signals. For a charged interface like silica–water interface, it is believed and shown that there are bulk (3) contributions from the electric double layer/diffuse layer near the silica–water interface.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Here we studied nonionic surfactants and water at the silica–surfactant solution interface. SFG is a surface-specific second-order nonlinear optical spectroscopy probing second-order nonlinear susceptibility χ (2) of a medium, which has been developed into a powerful tool to investigate surfaces and interfaces. We have applied SFG to study a variety of complex surfaces and interfaces including biological molecules, polymers, as well as surfactants. , The silica–water interfaces have been extensively studied by SFG in various aspects. Silanol groups on a silica surface can be deprotonated in an aqueous solution under neutral pH (SiOH ⇄ SiO – + H + ), which results in a negatively charged silica surface in contact with water. , Different surface structures of silica can form different types of hydrogen bonding with water at the buried silica–water interface, making water molecules ordered at the immediate silica–water interface (the nearest water layer on silica), which contribute to SFG signals. …”
Section: Introductionmentioning
confidence: 99%
“…Sum frequency generation (SFG) vibrational spectroscopy is a second-order nonlinear optical technique with intrinsic interface sensitivity. SFG has been extensively employed to study molecular structures of solid/liquid interfaces. We have demonstrated that the valuable molecular information for polymer/solution interfaces obtained by SFG can contribute to the elucidation of interfacial behaviors of polymer, water, and biological molecules. , To gain fundamental understandings of the interfacial behaviors in CFRP, SFG was applied to characterize the molecular structures of carbon fiber/sizing solution and plastic/sizing solution interfaces in this study.…”
Section: Introductionmentioning
confidence: 99%